Faktor Risiko Sanitasi Lingkungan dan Asupan Gizi terhadap Kejadian Stunting pada Balita (6-59 Bulan) - ., Rahmi Lisdeni; Hartono, Budi; Yusrin Putra, Wahyu Kurnia; Triyanti, Triyanti (Jurnal Sehat Mandiri, 2025)
Stunting remains a major public health issue in Indonesia, particularly in areas with poor environmental sanitation and inadequate nutritional intake. This condition affects linear growth in children, indicated by TB/U < –2 SD. This study aimed to identify risk factors associated with stunting among children aged 6–59 months related to environmental sanitation and nutritional intake in Batangkapas District, Pesisir Selatan Regency. A cross-sectional design was used with 189 children selected through cluster sampling. Data were collected through observation, interviews, STBM-based questionnaires, a semiquantitative FFQ, and anthropometric measurements. Data analysis included univariate, bivariate (Chi-square), and multivariate (logistic regression). The findings showed a stunting prevalence of 25.4%. Variables significantly associated with stunting included open defecation behavior, handwashing with soap, household food and water management, latrine ownership, and nutrient intake. Handwashing behavior was the most dominant factor with the highest odds ratio. The study concludes that poor environmental sanitation and inadequate nutritional intake are major risk factors for stunting. It is recommended that health centers and local health authorities strengthen STBM implementation, enhance nutrition education, increase provision of locally sourced supplementary feeding, and establish cross-sector collaboration to reduce stunting effectively.